Sejarah Kerajaan Turki Utsmani dan Kemajuannya Bagi Dunia Islam - Muhamad Basyrul Muvid (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2022)
Abstract The purpose of this study is to analyze the history and progress of the Ottoman Turks for the Islamic World. Historically, the founder of this kingdom was a Turkic nation from the Oghuz tribe, whose name was Ertugrul, he was the pioneer of the Ottoman Empire who died in 1289 AD. Later, the leadership was continued by his son, Uthman. Uthman bin Ertugrul is considered the founder of the Ottoman empire. There are nine phases, namely the first and second phases as the pioneering and founding phases of the Ottoman Empire, phases three and four as the glory phase, phases five to 8 as the phase of stagnation, decline and dissolution of the Ottoman Empire, while the ninth phase is the phase of the Republican caliphate. Factors that influenced the glory and progress of the Ottoman Turks were political, military, economic factors, the paradigm of rulers/sultans, and socio-political factors. Meanwhile, the territory of the Ottoman Turks in parts of Asia, North Africa to Eastern Europe can be conquered and maintained for approximately 6 centuries. The heyday of Solomon (King Solomon) was known by his people as the noble title "al-Qanuni". The forms of Ottoman progress were the military and government fields, science and culture, architecture, religion and political management. Abstrak Tujuan penelitian ini ialah untuk menganalisis sejarah dan kemajuan Turki Utsmani bagi Dunia Islam. Secara historis pendiri kerajaan ini adalah bangsa Turki dari kabilah Oghuz, yang bernama Ertugrul ia sebagai perintis kerajaan Turki Utsmani yang meninggal pada 1289 M yang kemudian, kepemimpinan dilanjutkan oleh puteranya yaitu Utsman. Utsman bin Ertugrul inilah yang dianggap sebagai pendiri kerajaan Utsmani. Ada Sembilan fase yakni fase pertama dan kedua sebagai fase perintisan dan berdirinya kerajaan Turki Utsmani, fase tiga dan empat sebagai fase kejayaan, fase lima sampai 8 sebagai fase stagnisasi, kemunduruan dan pembubaran kerajaan Utsmani, sedangkan fase sembilan sebagai fase kekhalifahan Republik. Faktor yang mempengaruhi kejayaan dan kemajuan Turki Utsmani di antaranya ialah faktor politikm, militer, ekonomi, paradigma penguasa/sultan, sosial politik. Sedangkan, wilayah kekuasaan Turki Utsmani wilayah dibelahan Asia, Afrika Utara hingga Eropa bagian Timur dapat ditaklukkan dan dipertahankan selama kurang lebih 6 abad. Masa kejayaan berada pada masa Sulaiman (King Sulaiman) dikenal oleh rakyatnya dengan sebutan mulia “al-Qanuni”. Adapun bentuk kemajuan Utsmani ialah bidang kemiliteran dan pemerintahan, ilmu pengetahuan dan budaya, bidang arsetektur, bidang keagamaan dan bidang manejeman politik.